A model investigation into the atmospheric NOy chemistry in remote continental Asia. (1st October 2019) - Han, K.M.; Lee, S.; Yoon, Y.J.; Lee, B.Y.; Song, C.H.
Abstract: The OMI-observed tropospheric NO2 columns over highly polluted regions in East Asia showed high values during the cold seasons and low values during the warm seasons. On the contrary, the monthly trends over Mongolia are completely opposite to those in polluted regions in East Asia. This study was initiated by such an interesting contrast. To determine the key factors controlling such monthly trends over Mongolia, we used the WRF-CMAQ simulated data. In the analysis, we explored the budget of P ‾ N O x (columnar net NOx chemical production rates), taking into account atmospheric chemical production and removal of NOx as well as surface (soil) NOx emissions. For the polluted regions, NOx emissions show the largest values, followed by P ‾ R N O 3 in terms of the magnitudes. Among the negative contributors, the largest contribution is made by P ‾ R N O 3 (columnar net NOx chemical production rates via the HNO3 and RNO3 -related reactions) ranging between −42% and −77% during the warm months. Other negative contributions from P ‾ P A N s (columnar net NOx chemical production rates via the formations and decompositions of PANs) and P ‾ H e t e r o . (columnar net NOx chemical production rates via the heterogeneous reactions of NO3 and N2 O5 ) are relatively small. Unlike the situations over the polluted regions, the negative P ‾ R N O 3 was offset completely by ENOx (emission of NOx ) and positive P ‾ P A N s over the remote continental regions of Mongolia. P ‾ P A N s was also regarded as an important atmospheric process, and its positive contributions range between 5% and 51% over the remote continental regions of (south) Mongolia. From the analysis, it was found that NO2 produced via thermal decomposition of PANs in the remote continental regions of Mongolia contribute to the high NO2 columns during the warm seasons and low values during the cold seasons. Graphical abstract: Image 1 Highlights: Monthly trends of NO2over Mongolia are opposite to those over polluted regions. Thermal decomposition of PANs is the primary reason for high NO2 in Mongolia during summer. Thermal decomposition of PANs can be major sources of NOx in Mongolia.